Immunosuppression of HLA identical living-donor kidney transplant recipients: A systematic review - VELİOĞLU, ARZU (My University, 2023)
Background: Kidney transplant (KT) recipients of HLA identical siblings (HLAid) have lower immunological risk, but there are no specific recommendations for immunosuppression. Our aim was to analyze evidence about results from HLAid living-donor recipients under different immunosuppression in the current era of immunological risk assessment. Methods: Systematic review of studies describing associations between outcomes of HLAid living-donor KT recipients according to their immunological risk and applied immunosuppression. Results: From 1351 studies, 16 (5636 KT recipients) were included in the analysis. All studies were retrospective, ten comparing immunosuppression strategies, and six immunological risk strata. Of those ten, six studies were published in 1990 or earlier and only three included tacrolimus. The evidence is poor, and the inclusion of calcineurin inhibitors does not demonstrate better results. Furthermore, only few studies describe different immunosuppression regimens according to the patient immunological risk and, in general, they do not include the assessment with new solid phase assays. Conclusions: There are no studies analyzing the association of outcomes of HLAid KT recipients with current immunological risk tools. In the absence of evidence, no decision or proposal of immunosuppression adapted to modern immunological risk assessment can be made currently by the Descartes Working Group.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TRANSPLANTASYON; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; TRANSPLANTATION; SURGERY; Cerrahi; Transplantasyon; Surgery; Transplantation; HLA-identical siblings; Immunological risk; Immunosuppression; Living kidney donation; Single HLA antigen beads